Heat and Mass Transfer Characteristics of a Desiccant Dehumidification System Operating by Low Regeneration Temperature. Issue 19 (8th September 2022) - Yaningsih, Indri; Wijayanta, Agung Tri; Miyazaki, Takahiko
Abstract: Heat and mass transfer characteristics (HMTCs), which defined the latent and sensible load, are essential for developing an effective desiccant dehumidification system (DSDHS). Therefore, the current work provides an investigation on the HMTCs, in the form of the Nusselt and Sherwood numbers. Under constant adsorption temperature of 293 K, the HMTCs were analyzed with three different regeneration temperatures of 308 K, 318 K, and 328 K. While the velocities were kept constant of 0.1 kg/s both for adsorption and regeneration processes. The DSDHS used the polymer material having the highest adsorption capacity of 0.78 kg/kg. Using the thermal and mass resistance approaches, the heat, and mass transfer coefficients were able to predict. The results show that the highest regeneration temperature revealed the most top differences between the humidity ratio inlet and outlet, which was 2.2 g/kg. The Nusselt number values, as well as Sherwood number, tend to increase with the rise of regeneration temperature. The proposed empirical correlation for predicting the HMTCs was followed by the experimental data with a maximum discrepancy of 17%. It is suggested that the properties of the interface must be carefully acquired to reduce the discrepancy between the experimental data and analytical.